Analisis Karakteristik Bakteri Probiotik - Iman Supriatna; Intannurfemi B. Hismayasari; I Gusti Ayu Bidiadnyani; Moh. Sayuti; Ahmad Yani (Jurnal Airaha, 2016)
This study aimed to identify and analyze the characterictics of probiotic bacteria. The method used was descriptive method to perform biochemical analyze on the type of probiotic bacteria derived from banana tree. Biochemical analyazed include Gram stain, catalase, oxidation, OF paraffin, OF non paraffin, citrate, ornithin, lysine, urea, MEVP, TSIA oblique, TSIA upright, lactose and sucrose. Results of laboratory analysis showed that the bacteria isolated in blood agar have the morphological characteristic of rod-shaped (bacil), gram-positive, can produce the enzym catalase, but it can not oxidize, it can not produce the enzyme citrate, ornithine, urease, These bacteria are acidic nature, able to ferment lactose and sucrose, and capable of produced acetone from glucose fermentation.